Factors Influencing Adoption of Drip Fertigation System Among Farmers: A Review - Ur Rehman, Zahoor; Ali, Maimunah (Research in Management of Technology and Business, 2022)
Integration of innovative irrigation systems and technologies is critical to improving crop water productivity and yields as global water levels fall and food demand rises. The drip fertigation system (DFS) is a resource conservation technology for agricultural production. Despite the numerous benefits of DFS, such as reduced water usage and increased crop productivity, DFS is still not widely used among farmers for farming practices. The purpose of this study was to conduct a detailed review to determine the factors that are hindering farmers from using drip fertigation system. The study revealed some key factors significantly contributing towards the adoption of drip fertigation system. Among these factors, water scarcity, availability of skilled operators or lack in technical skills, cost of installation and maintenance, subsidy from government, financial issues, and farmers’ awareness regarding drip fertigation system were the most significant factors effecting the adoption of drip fertigation system. The study provides some implications for government as well drip fertigation system providers to focus on these factors that can enhance the adoption of drip fertigation system in the near future.